Simulation of air pollution in Singapore - Lim, Chee Seng. (2011)
Air pollution, in recent times, has been a focus point in all parts of the world. Air pollutants are affecting all living mechanism one way or another. Hence, there is a need to determine the air pollutants as well as the distribution when subjected to weather condition at the area of study. This report studies the distribution of air pollutants in Singapore as well as the location of the sources which emits the pollutants. To study the air pollutants, the first priority is to identify the pollutants and the likely sources that it comes from. Industries, like refinery and powerplants are emitting pollutants as well as the transport that humans take to travel from one place to another. Industries that emit pollutants are known to be stationary sources while transport is known as area source due to frequent movement. Each source is known to emit certain amount of pollutants. Henceforth, there is a need to quantify these pollutants.